Construction of Large‐Area Uniform Graphdiyne Film for High‐Performance Lithium‐Ion Batteries. Issue 5 (14th December 2017) - He, Jianjiang; Bao, Kaijing; Cui, Weiwei; Yu, Jiaojiao; Huang, Changshui; Shen, Xiangyan; Cui, Zili; Wang, Ning
Abstract: Large‐area graphdiyne film is constructed by heat treatment, including thermally induced evaporation and a cross‐coupling reaction process. The growth mechanism is proposed based on the observation and characterization that the heating temperature plays an important role in the evaporation of oligomers and in triggering the thermal cross‐coupling reaction, whereas the heating duration mainly determines the execution of the thermal cross‐coupling reaction. By controlling the heat‐treatment process, a graphdiyne film with uniform morphology and good conductivity is obtained. The improved GDY film based electrodes deliver good interfacial contact and more lithium storage sites; thus leading to superior electrochemical performance. A reversible capacity of 901 mAh g −1 is achieved. Specifically, the electrodes exhibit excellent rate performance, with which a capacity of 430 mAh g −1 is maintained at a rate as high as 5 A g −1 . These advantages mean that the uniform graphdiyne film is a good candidate for the fabrication of a flexible and high‐capacity electrode material. Abstract : Turn up the heat ! A large‐area uniform graphdiyne (GDY) film has been constructed through thermal treatment for application in high reversible capacity lithium‐ion batteries (see figure). The heating temperature plays an important role in the evaporation of oligomers and in triggering the thermal cross‐coupling reaction, whereas the heating duration mainly determines the execution of the thermal cross‐coupling reaction.